Propagation of Atriplex halimus (Mediterranean Saltbush) in Multi-Contaminated Mine Tailings by Unrooted Cuttings - Marta Canu; Stefano Milia; Stefano Ubaldini; Elena Tamburini; Alessandra Carucci; Giovanna Cappai (Applied Sciences, 2025)
Phytotechnologies offer sustainable solutions for remediating mine residues by combining site rehabilitation with the potential recovery of secondary and critical raw materials (SRMs and CRMs, respectively), contributing to resource efficiency strategies. This study explored the direct propagation of Atriplex halimus unrooted cuttings into metal-contaminated mine tailings, assessing survival, biomass production, and trace metal accumulation. Treatments were carried out on mine tailings, with and without the addition of organic and inorganic amendments, and on commercial soil as a control. After an 8-week preliminary trial, Atriplex halimus demonstrated moderate survival and growth without phytotoxic symptoms, despite elevated trace metal concentrations. Significant accumulation of zinc, lead, and cadmium as model contaminants in the biomass of Atriplex halimus (up to 495.4, 31.9, and 1.2 mg kg−1, respectively), as well as magnesium and manganese as model CRMs (2081 and 87.8 mg kg−1, respectively) was observed in aerial tissues, comparable with traditional, though more labor-intensive propagation methods. Plants’ ability to accumulate metals was high in the presence of amendments added to promote biomass growth. These results highlight the significance of direct propagation by unrooted cuttings as a promising, low-cost strategy to initiate site restoration in metal-contaminated areas and warrant further investigation under field conditions and over longer durations.